Empowerment by enhancing the knowledge of community health center provider regarding the risks of preeclampsia - Hartatiek Nila Karmila; Mery Susantri; Ika Mardiyanti; Regina Ayu Fristiyanti; Nur Sophia Matin (University of Merdeka Malang, 2025)
Preeclampsia is the most common hypertensive complication during pregnancy. Additionally, preeclampsia is a leading cause of high morbidity and mortality rates. One of the healthcare professionals who plays a crucial role in providing health services to pregnant women at community health centers is the midwife and doctor. Therefore, it is necessary to strengthen the role of healthcare in community health centers to reduce the risk of morbidity and mortality due to preeclampsia. This community program aims to enhance the knowledge of midwives and doctors about preeclampsia particularly in terms of follow-up at both the primary and advanced levels. There are 74 midwives and doctors from the community health center in Surabaya participating in this event. This activity was carried out using the health education method combining discussions, and a Q&A session about preeclampsia. The measurement of knowledge levels was conducted using pre-test and post-test. From the results of the test, it was found that there was an increase in the average score of more than 50 percent. Based on the statistical test, the significance value in this study is 0.005 (p-value < 0.05). The results indicate that community programs can enhance the knowledge of midwives and doctors regarding preeclampsia effectively.